Water sources for root water uptake: Using stable isotopes of hydrogen and oxygen as a research tool in agricultural and agroforestry systems - Penna, Daniele; Geris, Josie; Hopp, Luisa; Scandellari, Francesca (Agriculture, ecosystems & environment, 2020)
•Knowledge on crop water uptake is required for sustainable agricultural management.•Stable water isotopes are powerful tools to study water sources for root uptake.•Many practical and research opportunities call for a broader use of this technique. Understanding water sources for crop water uptake in agricultural and agroforestry systems is an essential step to develop more efficient and sustainable water management strategies, which is increasingly important in the light of current world population growth, changing climatic conditions and consequent growing pressures on agricultural- and agroforestry production. Stable isotopes of hydrogen and oxygen in the water molecule are powerful and, nowadays, affordable tracers that can help to define the proportion of water sources accessed by plants. Yet, contrary to natural environments, their application is still relatively limited in agricultural and agroforestry research. In this work, we synthesize the advantages and the current knowledge deriving from the use of the stable isotopes of hydrogen and oxygen, in support of more traditional techniques, to understand root water uptake dynamics in agricultural and agroforestry systems. We also underline the practical implications related to the application of this technique for management purposes, and provide a vision for new challenges and future research opportunities in exploring crop and plant water use based on isotopic data.